Kajian Pembelajaran Bahasa (Psikolinguistik) Di UPT SMA Negeri 12 Bulukumba - Kaharuddin Kaharuddin; Yuliartati Yuliartati (Jurnal Keguruan dan Ilmu Pendidikan, 2021)
The success of language learning will depend on components involed in learning. These components include are students as learning subjects and language learning materials being studied by students. Therefore, in language learning the understanding of psycholinguistics is considered important. Through psychology it is learned about students and through linguistics leamed about language material through this interdisciplinary the process that occurs in students when understanding the material can be understood language.